Identifying Factors Contributing to Medical Errors: A Qualitative Study - Fatemeh Leyci; Faramarz Pourasghar (Taṣvīr-i salāmat, 2025)
Background. Medical errors present a significant challenge in healthcare systems, impacting patient safety and the quality of care. This study aimed to identify and prioritize the factors contributing to medical errors at Alzahra Teaching Hospital in Tabriz, Iran. Methods. This qualitative study employed an inductive content analysis approach and utilized multiple methods, including document reviews, focus group discussions, and expert panels. A purposive heterogeneous sampling method was used to select participants from various healthcare professional groups (including physicians, nurses, and midwives) with diverse work experience, age, and gender, representing a wide range of perspectives and experiences. To enhance the study's rigor, member checking was conducted. To prioritize the identified factors, an expert panel (11 members with over five years of experience) rated the importance of each factor on a scale of 1 to 10. The average scores were calculated, and factors were ranked accordingly. Results. The analysis identified 11 main categories, 45 themes, and 80 subthemes. The most significant category, provider-related factors, included a lack of knowledge and skills. Other categories involved communication failures, poor organizational culture, high workload, and outdated equipment. A total of 25 healthcare professionals (13 physicians, six nurses, and six midwives) participated in the study. The main categories (factors), in order of importance, included healthcare providers (10 themes), communication and information (five themes), organizational issues (eight themes), work environment (five themes), documentation (two themes), tasks (six themes), equipment (six themes), patients (four themes), and other categories including error reporting, and financial/legal issues (each comprising two themes). Conclusion. Findings indicate that care provider-related factors, especially lack of knowledge and skills, have the greatest impact on medical errors. To reduce these errors, it is recommended to design continuous education programs for healthcare staff, strengthen teamwork culture and interdepartmental communication, increase staffing, and upgrade medical equipment. These measures can significantly improve patient safety and quality of care.